SOSIALISASI LITERASI PRODUCT QUALITY COUNTER ACESSORIES HANDPHONE DI RPTRA KELURAHAN PAPANGGO KECAMATAN TANJUNG PRIOK JAKARTA UTARA - Zalukhu, Meschadin Bri Iman; Harianja, Elma Sari Serephina; Hidayat, Koerniawan (Jurnal Abdimas Bina Bangsa, 2025)
The counter business is engaged in products and services, namely selling cellphones, accessories, pulses and the internet. In this case, consumers are always looking for products that are often considered the best and fulfill consumer desires. So that the counter is required to make customer satisfaction the main goal in business. Consumer desires that always follow the development of the developing trend method. This requires companies or business people to also implement a good marketing strategy. The method of implementing community service, through the socialization of product quality literacy of hanphone accessories at RPTRA Lestari Indah Krlurahan Papanggo Tanjung Priok North Jakarta on January 22, 2025 with participants of administrators and members of RPTRA Lestari Indah and mothers of PKK Papanggo Village. Location and marketing strategies are important for discussion in establishing a cellphone counter company. The conclusion was the enthusiasm of the participants in establishing a cellphone counter company.